Recent Trends in Composite Nanozymes and Their Pro-Oxidative Role in Therapeutics - Maddheshiya, Shilpa; Nara, Seema (Frontiers in Bioengineering and Biotechnology, 2022)
Nanozymes are inorganic nanostructures whose enzyme mimic activities are increasingly explored in disease treatment taking inspiration from natural enzymes. The catalytic ability of nanozymes to generate reactive oxygen species can be used for designing effective antimicrobials and antitumor therapeutics. In this context, composite nanozymes are advantageous particularly because they integrate properties of various nanomaterials to offer a single multifunctional platform combining photodynamic therapy (PDT), photothermal therapy (PTT) and chemodynamic therapy (CDT). Hence, recent years have witnessed great progress in engineering composite nanozymes for enhanced pro-oxidative activity that can be utilized in therapeutics. Therefore, present review traverses over the newer strategies to design composite nanozymes as pro-oxidative therapeutics. It provides recent trends in the use of composite nanozymes as antibacterial, antibiofilm and antitumor agents. This review also analyzes various challenges yet to overcome by pro-oxidative composite nanozymes before being used in field.